Covert surveillance of communications: Compliance with the practice of the European court of human rights - Kovačević Milica (Anali Pravnog Fakulteta u Beogradu)
The paper deals with the protection of privacy rights in the connection with the application of special investigative actions in criminal proceedings. An increasing number of cases of the European Court of Human Rights in relation to Article 8 and the protection of privacy rights points out to the importance and complexity of this issue. On the one hand, public authorities should provide mechanisms and resources for effective and expeditious prosecution of the most serious forms of crime, but on the other hand, standards related to predictability, limited discretionary powers and control over the legality of the procedure should not be ignored either. This raises the question of how to achieve a balance between these competing interests. This paper presents the standards created by the European Court of Human Rights when dealing with privacy issues in connection with criminal proceedings, and reflects at the the degree of compliance of Serbian legislation with them. The author concludes that the key problem is the nonexistence of notification for the interested person, given that it implies the inability to exercise the right to appeal, and also the inability to put examples of bad practice to good use.